STRATEGI PROMOSI MELALUI MEDIA SOSIAL TERHADAP KEPUTUSAN PEMBELIAN SMARTPHONE MEREK XIAOMI YANG DI MEDIASI WORD OF MOUTH PADA MAHASISWA UNIVERSITAS SAMUDRA - Hidayat, Rahmad; safrizal; Lindung Bulan, T. Putri (Jurnal Mahasiswa Akuntansi Samudra, 2023)
This research aims to determine the influence of promotional strategies on purchasing decisions for Xiaomi brand smartphones mediated by word of mouth among students at Samudra University. This research used a sample of 96 respondents who were consumers of Xiaomi smartphone users. The data analysis method uses path analysis, t test, and coefficient of determination test. The results of this research show that promotional strategies via social media directly influence word of mouth, promotional strategies via social media influence purchasing decisions, word of mouth directly influences purchasing decisions, and promotional strategies via social media indirectly influence decisions. purchase of Xiaomi brand smartphones mediated by word of mouth. This research still has limitations in the form of a sample that is still less representative of the total population. It is recommended for future researchers to use a larger sample.